GAMBARAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING UNTUK SISWA YANG MEMILIKI MOTIVASI BELAJAR RENDAH DI SMP NURUL HIDAYAH PASUNDAN CIANJUR PADA MASA COVID-19 - lisna salisatul zanah; Nandang Rukanda; Tita Rosita (IKIP Siliwangi, 2022)
The learning process will run well if students have good motivation. This study aims to determine the illustration of student motivation in class VIII at Nurul Hidayah Middle School, Pasundan, Cianjur. The method used in this research is descriptive qualitative case study. The data collection is using interview, observation and documentation techniques. From the results of the data analysis, group guidance services have been provided with role playing techniques through several stages and are going well. In this problem the counseling guidance service used is group guidance service. The description of group guidance service activities with role playing procedures or role games is a learning strategy as part of a coordinated recreation in creating various opportunities for social-social change, creating real events or events that may arise in the future. By using the process of imagination, all students can be involved in the execution, besides the strong developments made by students will make it easier for students to understand the core of the material given.Keywords: Group Guidance, Role Playing Techniques, Learning Motivation